JARINGAN EKONOMI-POLITIK DAN MOBILISASI SOSIAL BAZAARIS PADA PERSIAN SPRING 2009 - Bakhtiar Ramadhan, Reza; Burdah, Ibnu; Yunus Masrukhin, Mohammad (Penamas, 2024)
This article examines the involvement and role of bazaaris in the Persian Spring from 2009 to 2011. As economic actors, these bazaaris participated in political activities that opposed Ahmadinejad’s victory in the Iranian presidential election. This rejection sparked mass mobilization, fueled by religious fervor, political and social ideologies, and economic concerns. The qualitative research approach employed in this study utilizes political sociology, drawing data from literature reviews and digital fieldwork. The data analysis conducted in this research employs the theory of conflict and mass mobilization, yielding two significant findings. First, it reveals that the political-economic network of bazaaris is cross-border and multi-dimensional. Second, it highlights that the mass mobilization of bazaaris against Ahmadinejad is primarily motivated by political and economic competition. Consequently, the findings of this study contribute to enriching the discourse of political sociology, particularly in conceptualizing popular resistance movements against authorities based on political-economic conflicts. These conflicts are intricately woven into the fabric of magnetic field politics, which tend to be transactional in nature.